Hydrothermal Extraction of Microalgae Fatty Acid Influences Hydrochar Phytotoxicity - Ennis, Christopher J.; Clarke, Joyce; Neate, Katherine; Cerejeira, Joana; Tull, Lewis (Frontiers in Environmental Science, 2017)
Hydrothermal carbonization (HTC) of microalgae biomass for the production of triacylglycerides is a potentially valuable enabling technology for a waste water treatment-based integrated biorefinery. Here, HTC was used to treat Phaeodactylum tricornutum lipid-rich biomass producing a solid hydrochar from the surface of which adsorbed lipids were removed by hexane extraction following filtration of the solid hydrochar from the process liquid product. Approximately 7% of the input biomass was recovered and transesterified for qualitative and quantitative GCMS analysis for fatty acid methyl esters. Transesterifiable lipids accounted for 94% of the material recovered by solvent extraction. Of the transesterified fatty acids (FA) analysed, the majority was monounsaturated (40.4%) and saturated (37%) C-16 FA. Other FA detected included saturated and monounsaturated C-18 (7.7% and 1.9%) and saturated C-14 (5.3%) and C-25 (1.5%). Thermal analysis (TGA/DSC) of the hydrochar in air showed calorific values of 10.6 MJ kg-1 (delipidated hydrochar) and 3.1 MJ kg-1 (non-delipidated hydrochar) with the latter exhibiting the presence of volatalisable components. Germination trials were conducted to assess the potential phytotoxic effects of these hydrochars. Delipidated hydrochar showed a germination index of 73% suggesting the presence of some phytotoxicity. Non-delipidated hydrochar showed high germination index results of 102% (unground) and 126 % (ground). Taken together with the observation of reduced root hair proliferation in these two test conditions, this suggests the operation of a second phytotoxic effect that is removed by delipidation.